Ten Myths About Law School Grading - Daniel L. Keating (Washington University Law Quarterly, 1998)
The myths that I describe below are held by students, faculty, employers, or some combination of the three. With each myth, I will endeavor to describe its content, its likely genesis, and then the countervailing truth about the same subject. I will begin with the myths that are primarily student-held and then proceed to describe faculty-held myths about law school grading.
Keywords: Law – Study & amp; teaching; Grading (Education); Legal education